Endovascular thrombectomy for the treatment of ischemic stroke: An updated meta-analysis for a randomized controlled trial - Jia Feng; Zhihan Zhu; Ahmed Waqas; Lukui Chen (Journal of Neurorestoratology, 2021)
Objective:To evaluate whether endovascular thrombectomy combined with intravenous thrombolysis is superior to the standard treatment of intravenous thrombolysis for the treatment of ischemic stroke.Methods:A meta-analysis of 12 studies obtained by searching PubMed and Web of Science database was performed to determine whether the difference in mortality (within 7 days or 90 days), functional outcome (modified Rankin Scale, 0-2), hemorrhage (symptomatic intracerebral hemorrhage, and subarachnoid hemorrhage), and recurrent ischemic stroke rate at 90 days between patients who underwent mechanical intravenous thrombolysis with (intervention) and without (control) endovascular thrombectomy.Results:As compared with the control group, patients in the intervention group had lower 90-day mortality [summary risk ratio (RR) = 0.83, 95% confidence interval (CI): 0.69-0.99; n = 1309/1070], higher recanalization rate (RR = 2.24, 95% CI: 1.97-2.56; n = 504/497), better functional outcome (modified Rankin score: 0-2; RR = 1.41, 95% CI: 1.29-1.54; n = 1702/1502), and higher rate of subarachnoid hemorrhage (RR = 2.40, 95% CI: 1.45-3.99; n = 1046/875) without significant difference in the 7-day mortality (RR = 1.12, 95% CI: 0.84-1.50; n = 951/773), symptomatic intracranial hemorrhage (RR = 1.12, 95% CI: 0.82-1.54; n = 1707/1507), or recurrent ischemic stroke (RR = 0.90, 95% CI: 0.52-1.54; n = 718/506).Conclusion:Our results demonstrated that patients in the intervention group had lower mortality and better functional outcomes than the control group. Although patients in the intervention group had a higher rate of subarachnoid hemorrhage; hence, endovascular thrombectomy combined with intravenous thrombolysis is still a beneficial intervention for a defined population of stroke patients.